2003
DOI: 10.1002/bdra.10086
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Hoxb‐5 during human lung development and in congenital lung malformations

Abstract: Hoxb-5 expression during human lung branching morphogenesis, which is similar to that observed in mouse lung development, indicates that it plays a role in controlling airway patterning. This notion is supported by results from BPS and CCAM tissue, in which Hoxb-5 is maintained in a manner typical of an earlier developmental stage and is associated with development of abnormal lung tissue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
72
0
6

Year Published

2003
2003
2009
2009

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 110 publications
(88 citation statements)
references
References 33 publications
(53 reference statements)
10
72
0
6
Order By: Relevance
“…In mice, we have reported that regulated spatial and temporal expression of the Hox protein, Hoxb5, helps regulate airway branching patterns partially through regulation of cell matrix molecules (57,60,61). We have also shown that HoxB5 (nomenclature for human Hoxb5) is expressed in human lung development in a similar pattern to that seen in mouse and that human BPS and CCAM tissue has abnormally high levels of HoxB5 protein, analogous to the canalicular stage of lung development and significantly increased over age and lung development stage-matched controls (59,64). The persistent overexpression of HoxB5 in BPS and CCAM tissues may have deleterious effects on downstream genes governing mesenchymal-epithelial cell adhesion and cellular interactions, but whether Hox gene regulation and altered cell adhesion coexist in BPS and CCAM has not been studied.…”
supporting
confidence: 52%
See 4 more Smart Citations
“…In mice, we have reported that regulated spatial and temporal expression of the Hox protein, Hoxb5, helps regulate airway branching patterns partially through regulation of cell matrix molecules (57,60,61). We have also shown that HoxB5 (nomenclature for human Hoxb5) is expressed in human lung development in a similar pattern to that seen in mouse and that human BPS and CCAM tissue has abnormally high levels of HoxB5 protein, analogous to the canalicular stage of lung development and significantly increased over age and lung development stage-matched controls (59,64). The persistent overexpression of HoxB5 in BPS and CCAM tissues may have deleterious effects on downstream genes governing mesenchymal-epithelial cell adhesion and cellular interactions, but whether Hox gene regulation and altered cell adhesion coexist in BPS and CCAM has not been studied.…”
supporting
confidence: 52%
“…We evaluated ␣ 2 -integrin protein levels in mouse fetal lung fibroblasts in which we have previously reported siRNA-specific downregulation of Hoxb5 protein. This was done to further understand the potential relationship between altered ␣ 2 -integrin protein expression in BPS and CCAM and the aberrant expression of HoxB5 protein that we have previously reported in these same tissue samples (59,60). Compared with mouse fetal lung fibroblasts treated with scramble siRNA (50 nM) (negative control), the 150-kDa protein isoform of ␣ 2 -integrin was significantly decreased in fetal mouse lung fibroblasts treated with Hoxb5 siRNA (50 nM) in association with the previously described decrease in Hoxb5 protein levels ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations